De novo metastatic breast cancer in patients with a small locoregional tumour (T1-T2/N0): Characteristics and prognosis. (November 2021) - Gaillard, T.; Carton, M.; Mailliez, A.; Desmoulins, I.; Mouret-Reynier, M.A.; Petit, T.; Leheurteur, M.; Dieras, V.; Ferrero, J.M.; Uwer, L.; Guiu, S.; Gonçalves, A.; et al.
Abstract: Introduction: The estimated rate of de novo metastatic breast cancer (dnMBC) at the time of diagnosis is between 5 to 12%. International guidelines recommend metastatic work-up (MWU) only in women with advanced breast cancer. The purpose of this study was to describe the characteristics and prognosis of patients with dnMBC diagnosed without an initial indication for MWU. Methods: We conducted a retrospective, comparative study in dnMBC patients selected from the ESME-MBC cohort. Patients were treated in France between 2008 and 2016. We compared two populations: patients in whom dnMBC was diagnosed by staging although not indicated by guidelines (non-guideline staging [NGS]) and those in whom dnMBC was diagnosed by guideline staging (GS). Results: During the study period, 22, 463 patients with MBC were included in the ESME cohort. Among them, 6698 were dnMBC patients. In 247 of these patients (6% of dnMBC and 1% of the overall population), dnMBC was diagnosed by non-guideline staging. Women in this group were significantly younger (57 vs. 59 years, p = 0.02) and had fewer metastatic sites at diagnosis than dnMBC-GS patients. The two groups were not significantly different in terms of the other characteristics. Overall survival (OS) and progression-free survival (PFS) were better in the dnMBC-NGS group than in the dnMBC-GS group. The impact on survival was confirmed by univariate and multivariate analysis (HR 1.83 [1.31–2.57], p < 0.01). Conclusion: This study provides the first description of a very specific population. These patients with dnMBC-NGS were younger and more likely to have oligometastatic disease with a better prognosis. Highlights: T1/T2 N0 de novo metastatic breast cancer (MBC) represented 6% of all de novo MBC. Metastatic diagnosis in this population implied an unrecommended workup. These patients were younger with oligometastatic disease and had a better prognosis. Locoregional therapy prior to diagnosis in this population did not change survival.